new Fourier transform approach for protein coding measure based on the format of the Z curve - Yan, M; Lin, Z.S; Zhang, C.T (Bioinformatics (Oxford, England), 1998)
MOTIVATION: At the core of most protein gene-finding algorithms are the coding measures used to make a decision on coding/non-coding. Of the protein coding measures, the Fourier measure is one of the most important. However, due to the limited length of the windows usually used, the accuracy of the measure is not satisfactory. This paper is devoted to improving the accuracy by lengthening the sequence to amplify the periodicity of 3 in the coding regions. RESULTS: A new algorithm is presented called the lengthen-shuffle Fourier transform algorithm. For the same window length, the percentage accuracy of the new algorithm is 6-7% higher than that of the ordinary Fourier transform algorithm. The resulting percentage accuracy (average of specificity and sensitivity) of the new measure is 84.9% for the window length 162 bp. AVAILABILITY: The program is available on request fromC.-T. Zhang. Contact: ctzhang@tju.edu.cn